Outcomes of septorhinoplasty: a new approach comparing functional and aesthetic results. Issue 2 (February 2018) - Radulesco, T.; Penicaud, M.; Santini, L.; Thomassin, J.-M.; Dessi, P.; Michel, J.
Abstract: The aim of this study was to compare objective and subjective functional results of septorhinoplasty with subjective aesthetic results. A prospective study was performed including global and subgroup analyses (primary versus secondary septorhinoplasty). Three instruments were used to evaluate pre- and postoperative results: rhinomanometry for the objective functional analysis, the Nasal Symptom Obstruction Evaluation (NOSE) scale for the subjective functional analysis, and the Rhinoplasty Outcome Evaluation (ROE) scale for the subjective aesthetic analysis. A septorhinoplasty was performed in all cases. Thirty-five patients were included (22 female), of whom 74% underwent primary septorhinoplasty. The correlation between rhinomanometry, NOSE and ROE scores was analysed. Mean resistance of the two nasal cavities was 4.9 (standard deviation (SD) 8.35) sPa/ml before surgery and 0.8 (SD 0.7) sPa/ml after surgery. NOSE and ROE scores were, respectively, 72.5/100 (SD 21.7) and 7.5/24 (SD 11.3) before surgery and 22/100 (SD 20.6) and 18/24 (SD 17.3) after surgery. Patients complaining of postoperative nasal obstruction had a worse aesthetic evaluation. Correction of the functional disease appears to be as important as aesthetic correction. This study comparing functional and aesthetic results after septorhinoplasty could provide a basis for future studies.